2014
DOI: 10.1159/000362682
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Fine Needle Aspiration of Axillary Lymph Nodes in Breast Cancer: Clinical Utility, Diagnostic Accuracy and Potential Pitfalls

Abstract: Objective: This study evaluates the diagnostic accuracy of axillary lymph node fine needle aspiration (FNA) cytology in breast cancer and correlates it with clinical parameters/outcomes. Study Design: A total of 91 females underwent FNA of axillary lymph nodes at our institution from January 2007 to February 2013. The cases were classified as ‘positive', ‘negative for malignancy' and ‘nondiagnostic'. Results: Forty-six cases (50.5%) had a histologic follow-up (4.4 ± 3.1 months); of these, 22 (47.8%) were true … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 21 publications
5
21
2
1
Order By: Relevance
“…The results of this study confirm, with a positive predictive value of 99.6%, the clinical utility of FNAC to direct treatment when the patient has a positive C5 FNAC. Other studies report a similarly low false‐positive rate of FNAC (0%‐1.6%) . Potential explanations for false‐positive FNACs include cytologic misinterpretation (eg, misreading myoepithelial cells or lymphocytes as breast epithelial cells) or inadequate sampling of the lymph nodes at the time of surgical dissection .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The results of this study confirm, with a positive predictive value of 99.6%, the clinical utility of FNAC to direct treatment when the patient has a positive C5 FNAC. Other studies report a similarly low false‐positive rate of FNAC (0%‐1.6%) . Potential explanations for false‐positive FNACs include cytologic misinterpretation (eg, misreading myoepithelial cells or lymphocytes as breast epithelial cells) or inadequate sampling of the lymph nodes at the time of surgical dissection .…”
Section: Discussionmentioning
confidence: 76%
“…Other studies report a similarly low false-positive rate of FNAC (0%-1.6%). 9,11,19,[26][27][28][29]…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the patients are summarized in Table 1 Several studies showed the sensitivity of FNAC varying from 48% to 92%, the specificity ranging from 94% to 100%, the PPV ranging from 83% to 100%, and the NPV ranging from 59% to 78%. [9][10][11][12][13][14][15][16] False-negative rates in the literature were reported to be between 8% and 24%. [12][13][14][15][16][17][18] The main reason for false-negative FNAC results appears to be the small size of the metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been performed to define the value of axillary FNAB as a diagnostic test in patients with primary breast cancer with reported sensitivity and specificity figures ranging from 40 to 91% and 90 to 100%, respectively [13-25]. …”
Section: Resultsmentioning
confidence: 99%
“…Axillary micrometastases may also contribute to the moderate false negative rate associated with FNAB [11, 13, 21]. …”
Section: Resultsmentioning
confidence: 99%